UiTM signs Memorandum of Understanding (MoU) with THB Maintenance Sdn. Bhd. / Nor Azlan Othman and Nor Aziyah Bakhari - Othman, Nor Azlan; Bakhari, Nor Aziyah (2021)
A Memorandum of Understanding (MoU) has been signed between Universiti Teknologi MARA (UiTM) and THB Maintenance Sdn. Bhd. at the THB Maintenance Sdn. Bhd. Headquarters, Alor Star, Kedah. The signing of this MoU will create new opportunities for both parties. This collaboration is the perfect platform for borderless and global education where all parties will have the opportunity to generate new knowledge and ideas through various activities and projects involving students and staff of UiTM with the industry. This Moll will build a bridge between the academicians and industry players benefiting the staff and students as well as UiTM- THB Maintenance staff in the areas of research development, innovation, curriculum, CSR, human capital, technology and others.